Age matters if you are cheese, wine or a third molar: Correlating age with the indications for and complications following third molar removal. (21st December 2022) - Azher, Simra; Delpachitra, Seth N.; Kumar, Ricky; Chandu, Arun; Garg, Krati
Abstract: Objective: Advanced age is a well‐recognised risk factor for complications following third molar surgery. However, age is largely exempt as consideration in published guidelines regarding the indications for third molar removal. This cross‐sectional study aimed to examine changes in the indications for third molar removal with increasing age. Materials and Methods: This was a retrospective cross‐sectional study of 500 consecutive patient records totalling 1446 third molar extractions. The primary measures examined were the patient's age and the surgeon's documented indication for third molar removal. Secondary measures included gender, smoking status, IAN proximity, number of teeth extracted per patient, and short‐term postoperative outcome. Results: Older patients were significantly more likely to undergo third molar extraction for periodontal disease and caries of adjacent teeth. Prolonged socket pain at 2 weeks was the most common complication encountered by patients across all age groups. Adults below age 25 were 1.69 times more likely to have uneventful healing ( p  < 0.02). Conclusion: Older patients are more likely to experience a slower postoperative course following third molar removal, as well as increased complications. Prophylactic removal of symptom‐free third molars may be justified to prevent adjacent caries, periodontal disease and odontogenic infections later in life.